Highly Dispersed Carbon Supported PdNiMo Core with Pt Monolayer Shell Electrocatalysts for Oxygen Reduction Reaction. (26th March 2018) - Okoli, Celest; Kuttiyiel, Kurian A; Sasaki, Kotaro; Su, Dong; Kuila, Debasish; Mahajan, Devinder; Adzic, Radoslav R.
Abstract : The development of low-cost, durable, and high-performance materials that could substitute for the current platinum-based electrocatalysts would accelerate the commercialization of polymer electrolyte membrane fuel cells as an alternative power source. We report herein a new fabrication approach of carbon-supported platinum monolayer (ML) on ternary palladium-nickel-molybdenum core electrocatalysts (PtML /PdNiMo/C) by a sonochemical method using ionic liquid (IL) as a dispersion medium. The sonolysis technique can control the size and distribution of the ternary-metal nanoparticles on different carbon supports without addition of any external reducing agents, surfactants or capping agents. Depositing Pt MLs using under-potential deposition method on the ternary PdNiMo nanoparticle cores could enhance activity and durability of the cathode during the oxygen reduction reaction of the fuel cell. Herein, we show that the described sonolysis method produces more reliable and cost-effective electrocatalysts that outperforms a commercial Pt-based catalyst.